Perkembangan Pariwisata Kota Langsa Tahun 2014-2019 - Dina, dinaandriani; Anis, Madhan (Program Studi Pendidikan Sejarah - Universitas Samudra, 2024)
Tourism development is the right choice and action considering that Langsa City has a lot of potential and natural resources that can be developed to the fullest. The wealth of potential and natural resources opens up opportunities for tourism development in Langsa City. The trend of developing the tourism industry is a phenomenon that occurs not only in Langsa City but throughout Indonesia and even the world. This is reasonable considering the large value generated by this sector. This research was conducted with the aim of, (1) To find out the efforts made by the Langsa City government in the tourism sector? (2) To find out the development of Langsa City tourism in 2014-2019. In writing this thesis using the type of qualitative research. The data analysis technique was carried out using the steps of (1) data collection, (2) data reduction, (3) data display and (4) verification and conclusion. The results of the study show that tourism development efforts in Langsa City carried out by the Langsa City Government Dispora are carried out through efforts: (a) developing tourist destinations, (b) developing facilities and infrastructure, (c) carrying out promotional activities, and (d) increasing human resources. . In this development effort, the Langsa City Government Dispora as a policy maker is more of a facilitator. In its implementation, it uses APBK and OSTUS funding sources and collaborates with entrepreneurs and the private sector. The development of tourism provides benefits for the community in Langsa City, namely: opening up job and business opportunities, increasing people's income by trading or by working in tourist destinations, as well as reducing unemployment with the opening of new businesses, developing community mindsets in a positive direction towards tourism and the growing awareness of the love of cleanliness and its cultural values. also has an influence on culture such as changes in lifestyle due to the effect of imitating tourist habits, changes in values, starting to be able to avoid misunderstandings in communicating and socializing, mutual respect for cultural differences and growing love for one's own culture.